(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In this article are mentioned some features of the ecology of the area, biology and morphological characteristic of the bleaks that belong to the alien species category for the settling reservoirs. There are given the analysis of the modern status of the “invader’s” population, its influence to the ichtyocenosis of the settling reservoirs and also the degree of the biological diversity. There are worked out its role in the ecosystems of the reservoirs of the Upper-Irtysh basin and the prospects of its usage in farm.